Effect of Angiotensin II on the Left Ventricular Function in a Near-Term Fetal Sheep with Metabolic Acidemia. (31st October 2011) - Acharya, Ganesh; Huhta, James C.; Haapsamo, Mervi; How, Ole-Jakob; Erkinaro, Tiina; Räsänen, Juha
Abstract : We tested the hypothesis that, in acute metabolic acidemia, the fetal left ventricle (LV) has the capacity to increase its contractility in response to angiotensin II infusion. Eleven ewes and their fetuses were instrumented at 127–138/145 days of gestation. The effect of angiotensin II on fetal LV function was assessed using intraventricular pressure catheter and tissue Doppler imaging (TDI). Angiotensin II increased fetal arterial blood pressure, whereas pH and pO2 decreased. The heart rate and systemic venous pressure were not affected significantly. The LV end-diastolic and end-systolic pressures, as well asdP/dt max, increased. The TDI-derived LV longitudinal myocardial isovolumic contraction velocity and its acceleration and velocity during early filling were higher than those at baseline. The incidence of absent isovolumic relaxation velocity was greater during angiotensin II infusion. In summary, during acute metabolic acidemia, the fetal left ventricle could increase its contractility in response to inotropic stimulus even in the presence of increased afterload. The diastolic LV function parameters were altered by angiotensin II.